Maximal expected benefits from lowering cholesterol in primary prevention for a high-risk population. (1st December 2016) - Fanton-Aita, Fiorella; Matteau, Alexis; Iliza, Ange Christelle; Mitchell, Dominic; Guertin, Jason R.; Dubois, Anick; Dubé, Marie-Pierre; Tardif, Jean-Claude; LeLorier, Jacques
Abstract: Aims: The objective of this study was to estimate the maximal clinical benefit that could be reasonably expected from a cholesterol-lowering intervention. Materials and methods: We used a hypothetical population at high risk of cardiovascular disease events from three risk assessment models including the Framingham risk function, the Score Canada and the Pooled Cohort Risk Assessment Equations. Our source population were all 55-year-old smoking men with diabetes, hypertension and low HDL. From this population, we identified two different subpopulations named "high" and "low", referring to their cholesterol levels which were set at 8.60 and 4.14 mmol/L respectively. Both subpopulations were identified for each risk assessment model in order to estimate the maximal impact of lowering cholesterol on cardiovascular disease events. Results: Our extrapolations estimated that the maximal theoretical efficacy of a cholesterol-lowering intervention corresponds to a risk ratio ranging between 0.46 and 0.66 over a 10-year period. The number of events prevented during this period were between 21 and 29 per 100 patients which corresponds to a number needed to treat varying from 3.47 to 4.76. Conclusions: Our estimation showed the maximal clinical benefit that could be reasonably expected by an intervention that would lower total cholesterol in high-risk patients.